Impact of Globalization in Different Sectors of Commerce in India - Verma, Raj Kumar (Journal of Commerce and Trade, 2012)
Globalization is a widely defined word today used in every sphere of life be it economy, commerce management education. Today the world has shrunk and become a small global village. People are eager to know what is happening and changing the world, and are effected by it. Technology is the main driving force in the globalization, the new advance information technology has made a lot of impact on the economies of the world and changed them drastically in past two decades. Due to globalization we have open economies world wide, countries like China have also opened their gates for trade to the world and they are flourishing. Globalization has helped in promoting international cooperation and peace cases like India and Pakistan. Even the farmer have benefited from globalization-now they have increased yield and are getting better price for their product, in many parts of country like India the cultivators of potato, tomato have collaborated with ketchup, and chips makers. Now Indian farmers have international market for their mangoes, spices flowers, vegetables, fruits tobacco and pappads. This paper tells us how globalization has reduced cost of transport, decreased or abolished the control over capital market, formed free zones for caring out trade due to reducing payment of tariff or no tariff payment in some cases so goods and people can now travel easily to other countries, which has opened and helped in flourishing tourism it has become one of the booming industry.